ISSUES OF JUSTICE IN THE VIEWS OF ABU ABDULLAH RUDAKI - Adiz Abdullaevich Azimov (International Journal of Literature and Language Studies, 2026)
This article analyzes the views of Abu Abdullah Ja'far bin Adam Rudaki Samarkandi, a great Eastern thinker and poet known as the